ANALISIS PERENCANAAN LABA PADA HOTEL MANAU SAMARINDA TAHUN 2020 - Marwanto Marwanto; Farindika Metandi; Liani Sintya Dewi (Politeknik Negeri Samarinda, 2021)
The problem of this research is how to plan the profit by using analysis the profit planning of Manau Hotel Samarinda. This research uses least square method and the help of Microsoft Excel 2007 program for separating semi variable cost to be fixed cost and variable cost. The tool analyze used is by using Break Even Point method and Margin Of Safety. The result of this research are minimum sales to get profit target in 2020 is Rp 1.345.072.933 and by analyze the cost, volume and profit to produce useful information for management to plan the profit of room sales. Keywords : Profit Planning, Break Even Point, Margin Of Safety.